(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
Abstract: The article analyzes pedagogical practices carried out at the university, in acting classes, in a remote environment, during the pandemic. Students were invited to reflect on the attentional regimes most operative in contemporary society and investigate, in their homes and everyday spaces, a different perception regime structured around silence, pause, dilated time, and getting out of oneself and moving towards others. The individual creative experiences born in this new attentional environment were collectively analyzed, transforming the classroom into a laboratory where art appeared as a propitious place to imagine other worlds, less violent, individualistic, and anthropocentric.